ASSESSMENT OF SEISMIC STRENGTH OF RESERVOIRS INTENDED FOR OIL PRODUCTS (American Journal of Technology and Applied Sciences, 2026)
This study presents engineering solutions aimed at reducing the seismic vulnerability of reservoirs intended for petroleum products. Scientific and practical proposals have been developed to increase the seismic resistance of the reservoir and structural strengthening measures have been proposed based on numerical analyses performed in the LIRA-SOFT 10.12 software package.